The Role of Management Accounting in Risk Mitigation and Business Opportunity Exploration for Competitive Advantage - Hariyanti (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to analyze the role of management accounting in risk mitigation and business opportunity exploration as a strategy to create competitive advantage. Using a literature review and descriptive analysis approach, this research examines 17 scholarly articles carefully selected from an initial pool of 40 articles sourced from Google Scholar between 2003 and 2024. The results of the study indicate that management accounting plays a significant role in helping organizations recognize potential threats, manage operational risks, and capitalize on opportunities for product innovation and business process efficiency. Case studies from several large companies in Indonesia, such as Telkom Indonesia, Unilever, Gojek, and specific SMEs, highlight how management accounting can be strategically utilized to enhance competitiveness amid global competition and the digital era. This study implies that the adoption of the latest technology and management accounting training could be solutions to optimize this role. However, the study is limited to a literature review, necessitating further empirical research to strengthen these findings.